Electronic cigarette users' reactions and responses to a hypothetical ban of flavoured electronic cigarette liquids. (3rd November 2022) - Soule, Eric K; Mayne, Shannon; Snipes, William; Thomas, Luke; Guy, Mignonne C; Breland, Alison; Fagan, Pebbles
Background: Regulations have been proposed to limit e-cigarette flavours, but limited research has examined potential impacts of such policies. This study examined adult e-cigarette users' reactions to a hypothetical e-cigarette flavour ban. Methods: In 2019, a convenience sample of current e-cigarette users in the USA (n=81, 53.1% women, mean age=37.6, 59.3% dual users of cigarettes) completed an online concept mapping study. Participants provided statements describing anticipated reactions to a hypothetical policy in which only tobacco, menthol or unflavoured e-cigarettes were available for purchase. Seventy-one unique statements were generated. Participants sorted statements into thematic groups and rated statements on how likely they would be to have each reaction. Multidimensional scaling was used to identify thematic clusters of statements. Results: Twelve clusters were identified: negative reaction, take action against flavour limitation, youth prevention effectiveness perception, tolerance, acceptance, willingness to try new flavours, maintain vaping, reduce vaping, new flavours as vaping cessation transition, alternative sources for banned flavours, do-it-yourself mixing behaviours and alternative tobacco products. The highest rated cluster (negative reaction) described being angry or upset that flavours were banned, while the lowest rated clusters related to quitting/reducing e-cigarette use or switching to other tobacco products. Non-tobacco or non-menthol/mint flavoured e-cigarette users had higher ratings for clusters describing negative sentiment for the hypothetical policy. Conclusions: Some e-cigarette users may dislike an e-cigarette flavour ban; however, some e-cigarette users would likely be willing to use tobacco, menthol or unflavoured e-cigarette liquids with lower likelihood of quitting vaping or switching to other tobacco products.